The Application of Profile Matching Method in Decision Support System for Selection of Training Instructors (Case Study at IIB Darmajaya's Training Center) - Sutedi Sutedi; Hendri Purnomo; Nirmala Handayani (Prosiding International conference on Information Technology and Business (ICITB), 2019)
The Training Center is a technical operation unit responsible for organizing both locally  and internationally certified training programs at Institute Informatics and Business (IIB) Darmajaya. Locally certified training is home-powered and its certificate is issued by the Training Center. Internationally certified training, on the other hand, involves a collaboration with a certification services body and the certificate is issued by reputable organizations or companies such as Microsoft, Foresec, Adobe, etc. IIB Darmajaya’s Training Center currently has 67 instructors and experts and offers 32 training programs, either local or international. However, it experiences difficulty in selecting instructors for locally certified training programs since the lecturers who regularly act as instructors only hold international certification. For locally certified training, the instructors are directly appointed by the Director of Training Center, who often finds it difficult to match a training program to a suitable instructor. To solve the issue, this study couples profile matching method with a decision support system to build a viable option for making the right decision based on a set of predetermined criteria. The concept of profile matching method is basically to compare personal competence with expected instructor competence so as to determine the competence gap. The lower the gap is, the higher the score an individual can get, which means a greater chance to be appointed as an instructor. Profile matching has successfully produced reliable information on the rankings of prospective instructors.Keywords: training, instructor, profile matching